Islamic-themed graffiti: potentials of public art with Islamic attributes - Zakariya, Khalilah; Zainal Abidin, Norzalifa; Mansor, Mazlina; Che Man, Shaibatul Islamiah (IDOSI Publications, 2016)
The explorations of public art in cities and communities have received growing attention from artists, designers and the public. Graffiti is a type of public art that is often associated with a medium of creative expression in the public space. Today, graffiti with religious, cultural, political and environmental themes are visible on the walls and other built structures. This study explores the potentials of Islamic-themed graffiti as a medium to convey positive messages that are executed through the incorporation of Islamic art attributes. The aim of this paper is to examine the perceptions of the public towards two Islamic-themed graffiti artworks that were installed in the campus’ public space. The methods comprise of creating the artwork and conducting a survey questionnaire among 200 respondents that consist of Muslims and non-Muslims. The analysis revealed three key findings. First, the presence of Islamic elements and the message conveyed influenced the respondents’ perceptions of public art with Islamic attributes. Second, both graffiti artworks were regarded to make the public space lively. Third, Islamic-themed graffiti has potentials to act as a medium to spread positive messages. The study concludes that Islamic-themed graffiti can further be explored as a form contemporary Islamic public art.